An Application of Iterative Pushdown Automata to Contour Words of Balls and Truncated Balls in Hyperbolic Tessellations. (29th March 2012) - Margenstern, Maurice
Abstract : We give an application of iterated pushdown automata to contour words of balls and two other domains in infinitely many tilings of the hyperbolic plane. We also give a similar application for the tiling 5, 3, 4 of the hyperbolic 3D space and for the tiling 5, 3, 3, 4 of the hyperbolic 4D space as well.